Pengaruh Teknologi Digital Terhadap UMKM di Kota Padangsidimpuan - Wardani Gurning; Kapika Annisa (Universitas 45 Surabaya, 2024)
This study aims to analyze the influence of digital technology on Micro, Small, and Medium Enterprises (MSMEs) in Padangsidimpuan City. The study used a qualitative method with in-depth interviews with 12 MSME actors from various sectors, such as culinary, crafts, and trade. The focus of the study is the impact of digital technology on marketing, operational efficiency, and access to financing. The results of the study show that digital technology provides great benefits for MSMEs, especially in expanding the market through social media and e-commerce. However, challenges in the form of limited digital literacy and internet infrastructure still hinder its optimal utilization. This study provides recommendations in the form of digital literacy training and strengthening infrastructure as strategic steps to support the digital transformation of MSMEs in Padangsidimpuan.